PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR ILMU PENGETAHUAN SOSIAL - Mohammad Afifulloh Hasyim (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2019)
Social Studies aim to make good civic students. One indicator of good citizens is students can solve problems that occur in the surrounding environment. In an effort to deliver students to these goals, the learning process that takes place is always associated with the situation and conditions of the surrounding environment. The use of the environment as a learning resource helps students understand the problems in their environment and make them closer / closer, so that a sense of love for the environment arises.Â